2019
DOI: 10.1308/rcsann.2019.0037
|View full text |Cite
|
Sign up to set email alerts
|

Mortality for emergency laparotomy is not affected by the weekend effect: a multicentre study

Abstract: Introduction The ‘weekend effect’ describes variation in outcomes of patients treated over the weekend compared with those treated during weekdays. This study examines whether a weekend effect exists for patients who undergo emergency laparotomy. Materials and methods Data entered into the National Emergency Laparotomy Audit between 2014 and 2017 at four NHS trusts in England and Wales were analysed. Patients were grouped into those admitted on weekdays and those on weekends (Friday 5pm to Monday 8am). Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Considering the heterogeneity of patients presenting for emergency surgery, the decision-making process must not be influenced by the time of the surgery but be based on objective risk stratification score. [ 22 23 ] Similarly, in our hospital, oncology cases needing urgent surgery may not necessarily be sick to withstand surgery. Change in attitude towards pain management during after hours is not just a reflection of the experience, but a change in priority of the senior-most anaesthesiologist conducting the case.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the heterogeneity of patients presenting for emergency surgery, the decision-making process must not be influenced by the time of the surgery but be based on objective risk stratification score. [ 22 23 ] Similarly, in our hospital, oncology cases needing urgent surgery may not necessarily be sick to withstand surgery. Change in attitude towards pain management during after hours is not just a reflection of the experience, but a change in priority of the senior-most anaesthesiologist conducting the case.…”
Section: Discussionmentioning
confidence: 96%
“…Our study showed no significant differences in post-operative LOS and mortality with respect to the day of surgery (WE vs WD). Moreover, recent improvements in healthcare within the UK, including more protocol-based management of sepsis, better access to intensive care beds, and care for patients requiring emergency abdominal surgery, might have controlled the weekend effect [ 25 ]. Differences in staffing levels and availability of resources at weekends may explain the observed variability of weekend effects across the world; however, the current literature does not provide adequate evidence to compare the structure of the on-call emergency general surgery team on weekends in different countries and continents.…”
Section: Discussionmentioning
confidence: 99%
“…For specific surgical procedures, such as lysis of adhesions or partial colectomy, a higher postoperative mortality was observed for patients operated on the weekend [ 2 ]. However, patient data from different countries contradicted these results, showing no influence of the weekday on postoperative short- and long-term patient outcome [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that explain differences in risk adjusted mortality after general surgical emergencies in England have been identified, but the outcome measures relate to the day of admission not surgical treatment [ 7 ]. Of note, no difference in postoperative mortality by day of emergency general surgery has been observed [ 5 , 6 ]. Data on the quality of surgical treatment and oncological outcome of the resected patients is missing.…”
Section: Introductionmentioning
confidence: 99%